Discovery of pyrazole-3-carboxylic acid derivatives as dengue virus protease inhibitors with antiviral activity - Lang, Johannes; Koch, Jeannette; Dutta, Sudip K.; Leuthold, Mila; Martina, Byron; Klein, Christian D. (ACS medicinal chemistry letters, 2025)
We present the discovery of pyrazole-3-carboxylic acid derivatives as novel dengue virus (DENV) NS2B-NS3 protease inhibitors. The discovery was triggered by omission of the phenylglycine scaffold of previous lead structures. We established a robust, regioselective synthetic route toward pyrazole-3-carboxylic acid derivatives. Subsequent SAR studies delivered inhibitors with promising activity against the DENV protease in biochemical and reporter gene assays with EC50 values down to 2.2 μM and antiviral activity against DENV-2 with EC50 values down to 4.1 μM. Active site binding and target specificity were evaluated by a tryptophan fluorescence quenching assay. We further observed negligible cytotoxicity, no inhibition of the off-targets thrombin and trypsin, and promising early stage pharmacokinetic properties. The 2-aminopyrimidine scaffold was identified as a promising nonbasic replacement of the guanidine moiety. In addition, eliminating the highly hydrophobic phenylglycine moiety of previous compound series provides a crucial increase in drug likeness of this novel flaviviral protease inhibitor class.
Gesehen am 28.11.2025